Arahan Penataan Ruang Sempadan Sungai di Wilayah Perkotaan Kabupaten Bojonegoro - Endarwati, Maria Christina; Widodo, Widiyanto Hari Subagyo; Imaduddina, Annisaa Hamidah (Universitas Diponegoro, Indonesia, 2021)
Bojonegoro Regency is one of the areas traversed by the Bengawan Solo River and is at risk of flooding annually. Utilization of the land around the watershed becomes a special supervision in reducing the risk of this disaster. The purpose of this study is to determine the delineation of the area which is the locus of observation, so that the direction of spatial planning for riparian zone can be determined in the Bojonegoro and Kapas District, Bojonegoro districts. The method used in this study is to use qualitative analysis by analyzing typology or grouping, and comparisons between data and regulations / policies. Based on the results of the analysis and discussion that has been carried out, namely the identification of river formations, analysis of the typology of characteristics around the river to the determination of the riparian zone, a conclusion is obtained in the form of recommendations for spatial planning directions that need to be carried out in the riparian zone. The results obtained from this study are that Bojonegoro District is a flood-prone sub-district dominated by a moderate flood hazard area so that each cultivation activity has a conditional license, while Kapas District is a sub-district that does not have the potential for flooding because all river segments are in a flood-prone area. Low so that all cultivation activities in the Kapas District are permitted. With this study, it is hoped that it can help and become an input for the Bojonegoro Regency government in planning spatial planning, especially in the riparian zone in Bojonegoro and Kapas Districts.